Lipid Panel Predictors of Urinary Incontinence in Elderly in Bina Bakti Nursing - Tambunan, Nicholas Albert; Soni, Yulfitra; Santoso, Alexander Halim; Teguh, Stanislas Kotska Marvel Mayello; Alifia, Tosya Putri; Raharjo, Anthony Jason (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Urinary incontinence (UI) significantly impacts the quality of life in older adults, often resulting from multifactorial causes, including age-related changes and systemic health issues. Emerging evidence highlights the role of lipid metabolism in influencing bladder and pelvic floor function through vascular integrity, inflammation control, and tissue repair. Lipid parameters, such as apolipoproteins, HDL, LDL, total cholesterol, triglycerides, and their ratios, provide insights into metabolic health and its association with UI. This study aims to identify specific lipid-related predictors, advancing the understanding of metabolic factors in UI and informing targeted prevention and management strategies for aging populations. This study used multiple linear regression analysis to assess the relationship between lipid panel predictors and urinary incontinence in 93 elderly respondents at Bina Bakti Nursing Home. The analysis identifies apolipoprotein B, Apo B/Apo A ratio, total cholesterol, and triglyceride-to-HDL ratio as significant predictors. These variables actively influence urinary incontinence through metabolic and vascular pathways, with both positive and negative associations. Apolipoprotein B, Apo B/Apo A ratio, total cholesterol, and triglyceride-to-HDL ratio predict urinary incontinence, highlighting lipid-related impacts on vascular health, inflammation, and tissue integrity for improved risk stratification.